2001
DOI: 10.1007/s001670100194
|View full text |Cite
|
Sign up to set email alerts
|

360° arthroscopic capsular release in patients with adhesive capsulitis of the glenohumeral joint – indication, surgical technique, results

Abstract: Adhesive capsulitis of the glenohumeral joint is said to be a self-limiting process. However, in some patients the disease can last much longer than 1 year, which may lead patients to more invasive treatment than merely undergoing physiotherapy. Other patients do not accept this severe limitation and choose treatment options that restore the range of motion (ROM) more rapidly. Conventional open release techniques generally improve motion but involve extensive dissection. The purpose of this study was to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
92
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 25 publications
(49 reference statements)
0
92
0
6
Order By: Relevance
“…11,14 Numerous recent studies have supported arthroscopic release for effectively treating refractory adhesive capsulitis through the controlled release of the capsular restraints. [4][5][6]15 Glenohumeral motion loss assessed in cadaveric cutting studies has clarified that the regional capsule must be released. 16,17 Loss of external rotation mandated the release of the MGHL, rotator interval, coracohumeral ligament extra-articularly, or intra-articular portion of the subscapularis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,14 Numerous recent studies have supported arthroscopic release for effectively treating refractory adhesive capsulitis through the controlled release of the capsular restraints. [4][5][6]15 Glenohumeral motion loss assessed in cadaveric cutting studies has clarified that the regional capsule must be released. 16,17 Loss of external rotation mandated the release of the MGHL, rotator interval, coracohumeral ligament extra-articularly, or intra-articular portion of the subscapularis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent advances in arthroscopy, arthroscopic release of the joint capsule is more favorable than other treatment options. [3][4][5] However, the extent of release is still controversial. Several authors have recommended 360 release, whereas others have suggested a relatively conservative release.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Nicholson 5) showed good clinical outcomes in 68 patients with adhesive capsulitis after arthroscopic pancapsular release, and proposed that for an enhanced postoperative internal rotation, performing a posterior capsular release is recommended. Another study carried out Ide and Takagi 6) on 44 patients with adhesive capsulitis showed a successful outcome after pancapsular release.…”
Section: Discussionmentioning
confidence: 99%
“…the release of the rotator interval and the anteroinferior capsule, gives results that are comparable to the results after posterior capsular release. [5][6][7][8][9] To rule out one of the possiblility that selective capsular release alone could give clinical outcomes that are comparable to those of posterior capsular release for the treatment of adhesive capsulitis, we investigated whether selective capsular release and pancapsular release have any relative advantage over one another for the treatment of adhesive capsulitis in terms of the clinical outcome and range of motion (ROM).…”
Section: Introductionmentioning
confidence: 99%
“…7,8) However, the extent of release is still the subject of debate. Besides the CHL and rotator interval, some authors have recommended release of the subscapularis tendon, 9) inferior capsule, 10) posterior capsule, 11,12) or global capsule 13) to improve elevation and internal rotation (IR), as well as external rotation (ER). Pearsall et al 14) reported that information regarding preoperative motion loss would precisely direct selective capsular release.…”
Section: Introductionmentioning
confidence: 99%